2014
DOI: 10.1080/09650792.2014.904237
|View full text |Cite
|
Sign up to set email alerts
|

Meta-action research with pre-service teachers: a case study

Abstract: This article analyses a case of action research collaboratively conducted by a university teacher and 50 students in a master's course in teacher training. Its originality resides in the socio-economic, academic, and conceptual nature of the obstacles encountered in the module; in the meta-theoretical orientation of the action research that was chosen to overcome them; and in how triangulation strategies were devised to compensate for the limitations imposed by the academic framing of the course. In spite of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Such an exploration could thus offer benefits to teachers and teacher educators to better understand how emotions feature in AR and more importantly how emotions could be employed for contributing to teachers' professional growth in short and long terms. In this vein, our understanding of AR, thus, resonates with the recent scholarship (e.g., Banegas & Villacañas de Castro, 2019; Villacañas de Castro, 2014, 2020) in situating AR against the role of power and discourse in educational work (i.e., emotion labor), yet with a focal attention to how the process of AR is inflected with emotion work, as the under‐explored agendum in this line of thinking and research. The present study aimed to fill this gap by reporting on four Iranian English language teachers' engagement in AR, addressing the following question:…”
Section: Literature Reviewsupporting
confidence: 74%
See 2 more Smart Citations
“…Such an exploration could thus offer benefits to teachers and teacher educators to better understand how emotions feature in AR and more importantly how emotions could be employed for contributing to teachers' professional growth in short and long terms. In this vein, our understanding of AR, thus, resonates with the recent scholarship (e.g., Banegas & Villacañas de Castro, 2019; Villacañas de Castro, 2014, 2020) in situating AR against the role of power and discourse in educational work (i.e., emotion labor), yet with a focal attention to how the process of AR is inflected with emotion work, as the under‐explored agendum in this line of thinking and research. The present study aimed to fill this gap by reporting on four Iranian English language teachers' engagement in AR, addressing the following question:…”
Section: Literature Reviewsupporting
confidence: 74%
“…The literature of AR shows that researchers and more specifically teacher educators play a key role in the way AR unfolds in practice and in how teachers view their AR engagement (e.g., Villacañas de Castro, 2014; Yuan & Burns, 2017). In line with this understanding, we explain our positionality to elucidate the whole process of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher research can encompass action research (Burns, 2010;Dikilitaş & Griffiths, 2017) and exploratory practice (Allwright & Hanks, 2009;Hanks, 2017) and it is used as continuing professional development in Latin American countries such as Argentina (Banegas, Pavese, Velázquez, & Vélez, 2013), Brazil (Seixas Vial & Kurtz de Souza Welp, 2015, Chile (Burns, Westmacott, & Hidalgo Ferrer, 2016;Smith, Connelly, & Rebolledo, 2014), Mexico (Roux & Mendoza Valladares, 2014) and in other countries, for example Australia (Edwards & Burns, 2016b), China (Wang & Zhang, 2014;Yuan et al, 2016), or Turkey (Wyatt & Dikilitaş, 2015). Previous research reports how future teachers (Villacañas de Castro, 2014) and practising teachers engage in action research to bridge the so-called gap between theory and practice and produce context-responsive answers to their classroom concerns (Edwards & Burns, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…ALAR in graduate programs has proven to be an effective means to achieve high levels of personal growth when an integrated joint learning process between teachers and students is implemented (Villacañas de Castro, 2014). Additionally, several research studies have revealed the benefit of introducing the ALAR process in a practical, linear manner, providing step-by-step instructions, along with observing the organic, free-flowing process of ALAR (i.e.…”
Section: Alar For Development Of Leadership Capabilitiesmentioning
confidence: 99%